O SUJEITO TOXICÔMANO E A TOXICOMANIA - Zanfra, Ariele Rakoski; Daronco, Denise Mattioni; Aimi, Amanda Suelen; Pereira, Augusto Renan Cervo; Souza, Fabieli Da Silva; Guisso, Juliane (Salão do Conhecimento, 2018)
Trabalho desenvolvido e apresentado na disciplina de Aspectos Sociais do Sintoma